Extracorporeal hemocorrection in the treatment of liver failure - I. V. Aleksandrova (Трансплантология (Москва))
As of now, clinical stabilization during the time required for the spontaneous regeneration of the liver or its orthotopic transplantation is the optimum treatment strategy. The use of artificial hepatic function support systems reduces mortality in severe hepatic failure from 85 to 60%. According to the used technologies, these systems can be divided into biological, non-biological (artificial or cell-free technologies), bioartificial or hybrid devices. The positive and negative aspects of these technologies are shown in this review.